Presence of enterotoxigenic Staphylococcus aureus in artisan fruit salads in the city of San Luis, Argentina - Lucero Estrada, Cecilia S. M. (2013)
Fil: Lucero Estrada, Cecilia S. M. Universidad Nacional de San Luis. Microbiología General; Argentina.